Andean Utopia. Ideology and social struggles - Plasencia Soto, Rommel (2020)
This article discusses the use of the concept of “Andean Utopia” in the social sciences the 80s. Not only it was used to characterize the “cycle of revolts” of the Andean south the first decades of the 20th century and the rural struggles of 1950-1960; but also to explain in the first moment, the birth of Shining Path in Ayacucho. The reasons were between others, of using the theoretical arsenal of the anthropology an also of exotizar to the actors of the above-mentioned movements.